Some considerations to face COVID 19 in Cuba and its impact on preschool age - Pomares Ortega , Ursula Cristina; Rodríguez Gardó, Lesvia Leonides; Águila Turiño , Eduardo Rafael; Hernández Quesada , Mercedes Cecilia (Revista Minerva, 2021)
The Cuban system of Health has as purpose to rise more and more its capacity to satisfy the population's growing necessities and especially that of its infants. Before the appearance of the first case of the COVID-19, the Ministry of Public Health took the decision of displaying actions guided to protect the existent clinical rehearsals and to promote the development of new investigations with the purpose of having own treatments for the best treatment and these patients' handling before this pathology. For the realization of this investigation methods of scientific investigation were used as the historical-logical, with support of the technique of documental revision. The picked up information of investigations was revised registered in internet, the  Web site of the World Organization of  Health, the Cuban public registration of clinical rehearsals, as well as the last investigations emitted by the Granma newspaper. The work contributes some considerations related with different actions carried out in Cuba about the topic  object of study. Satisfactory results were obtained in the actions developed.
Keywords: quality of life; coronavirus; prescolar age; clinical rehearsals; pandemic